EFEKTIVITAS BIMBINGAN KELOMPOK MENGGUNAKAN MEDIA KARTU LITERASI UNTUK MENINGKATKAN MINAT MEMBACA SISWA DI SANGGAR BELAJAR PANDAN - Alti, Diadra Dewina; Sri Ngayomi Yudha Wastuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of group guidance using literacy card media in increasing students' reading interest at Sanggar Belajar Pandan. Low reading interest poses a serious challenge in Indonesian education, with UNESCO data showing a reading index of only 0.001. This research employed a quantitative approach with a One Group Pretest-Posttest Design involving 8 fifth-grade students. The research instrument was a validated reading interest questionnaire based on Burs and Lowe indicators in Prasetyono (2008). Data were analyzed using the Paired t-test to examine the mean score differences before and after intervention. Results showed a significant increase in students' reading interest after participating in group guidance with literacy card media. The mean pretest score of 65.2 increased to 78.5 in the posttest (p-value < 0.05). Literacy card media proved effective in creating an enjoyable and interactive learning atmosphere, encouraging students to be more active in literacy activities. This study provides practical contributions to developing literacy learning strategies in non-formal educational institutions.